2024
DOI: 10.3390/foods13060924
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum A72, a Strain with Antioxidant Properties, Obtained through ARTP Mutagenesis, Affects Caenorhabditis elegans Anti-Aging

Sibo Zou,
Qi Wu,
Zhigao Li
et al.

Abstract: This research endeavored to elucidate the antioxidant attributes of lactic acid bacteria, specifically their impact on anti-aging and lifespan augmentation in Caenorhabditis elegans. The study focused on Lactiplantibacillus plantarum A72, identified through ARTP mutagenesis for its potent antioxidant properties. In vitro analysis affirmed its free radical neutralizing capacity. In C. elegans, the strain not only extended the lifespan by 25.13% and amplified motility 2.52-fold, but also maintained reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Furthermore, PTIO • has also attracted much attention as a redox mediator for batteries [35][36][37]. Recently, it has been reported that PTIO • can be used to estimate the activity of antioxidants as a reactivity model of reactive oxygen species [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. However, there is no report on the reactivity of PTIO • in the presence of redox-inactive metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PTIO • has also attracted much attention as a redox mediator for batteries [35][36][37]. Recently, it has been reported that PTIO • can be used to estimate the activity of antioxidants as a reactivity model of reactive oxygen species [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. However, there is no report on the reactivity of PTIO • in the presence of redox-inactive metal ions.…”
Section: Introductionmentioning
confidence: 99%